Diagnosis of Retrograde Cricopharyngeus Dysfunction Using High Resolution Impedance Manometry and Comparison With Control Subjects - Raymenants, Karlien; Vulsteke, Friedel; Vanuytsel, Tim; Rommel, Nathalie; Baert, Filip; Delsupehe, Kathelijne; Bohyn, Alexandre; Tack, Jan; Arts, Joris (Clinical gastroenterology and hepatology, 2025)
Retrograde cricopharyngeal dysfunction (R-CPD) or inability to belch has been linked to ineffective relaxation of the upper esophageal sphincter (UES) during gastroesophageal gas reflux, and botulinum toxin (BT) injection into the UES has demonstrated success in case series. However, the diagnosis is often overlooked. High resolution impedance manometry (HRiM) with belch provocation was recently suggested as diagnostic tool. Our aim was to confirm manometric findings in patients with R-CPD before and after BT treatment and to compare with control patients and healthy volunteers. Retrospective analysis of HRiM with belch provocation was performed between May 2021 and April 2024. Gas reflux episodes were counted and analyzed for UES relaxation, air clearance, air entrapment, or oscillatory movements of air in the esophagus, among others. Fifty-five patients with symptoms suggestive of R-CPD, 30 control patients, and 15 healthy volunteers were included (n = 100). Twenty-nine patients had a repeat measurement after treatment with BT (n = 29). Median esophageal contractility was lower in R-CPD versus control patients and healthy volunteers (distal contractile integral: 146, 577, and 316 mmHg.cm.s, Padj = .0109). During belching, we saw higher UES pressures in R-CPD patients vs controls, leading to incomplete air clearance and air oscillating in the esophagus (P < .0001). After BT injection, median UES pressures during belching decreased (56 vs 3 mmHg), and air clearance improved (P < .0001). A maximum UES pressure during belching >31 mmHg adequately discriminated patients from controls. Rapid drinking challenge with sparkling water can serve as belch provocation test during HRiM, with higher UES pressures during gas reflux and oscillations discriminating R-CPD patients from controls. [Display omitted]